An Analysis of Biology Oral Communication Skills and Cognitive Learning Outcomes: The Impact of Practicum-Based Two-Stay Two-Stray Learning Model - Likita, Egy Razka; Maulina, Dina; Sikumbang, Darlen (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2020)
Oral communication skills and cognitive learning outcomes are indicators of learning achievement. This research aimed to analyze students' oral communication skills and cognitive learning outcomes through the implementation of practicum-based TSTS. This research employed the quasi-experimental method with a pretest-posttest control group design. The samples were determined using the purposive sampling technique. The results showed that the practicum-based TSTS learning model contributed to students' oral communication skills with excellent categories. Teaching and learning activities using the practicum-based TSTS affected students' cognitive learning outcomes (Sig. 0.838> 0.05). Thus, this research showed that the implementation of the practicum-based TSTS learning model on the Plantae topic can train students’ oral communication skills and affect their cognitive learning outcomes.